Diatom as forensic indicator: in vivo studies of ingested diatoms for interpreting diatom test results - Fuad, Wan Nur Syazwan Wan Mohamad (2016)
Diatoms have constantly been associated with the diagnosis of drowning in the field of forensic diatomology. The finding of diatoms in the bodies of non-drowned deceased has challenged the reliability of the diatom test as indicative of ante-mortem drowning. The availability of diatoms in the foodstuffs has been attributed to the possibility of diatoms to entering the systemic circulation via the gastrointestinal tract. Sprague – Dawley (SD) rats were used as animal models to understand the fate of ingested diatoms inside the human body while evaluating the reliability of the diatom test. A total of 60 SD-rats were equally divided into two groups, control and experimental, and each group was again divided into six batches of five rats in a batch. Three times a week, the experimental group was intragastrically administered with metered-doses diatom frustules from a stock solution. Every two months one batch from control and one batch from experimental groups were sacrificed and the internal organs were harvested. The harvested organs were digested with concentrated nitric acid and after repeated centrifugation, the resulting sediment was microscopically examined. The number of diatoms, intact and fragments, recovered from the digested organs was counted and recorded. Diatoms were recovered from the liver, heart, brain, kidneys and lungs from the animals of the experimental group alone although the number was small, the maximum being 14 from the liver from animals of the sixth batch. The recovery ofdiatoms from the internal organs of the experimental animals proved that the ingested diatoms can enter into the systemic circulation via gastrointestinal lining. The above finding of this research necessitates a paradigm shift in treating diatoms as indicators of ante-mortem drowning when frustules are recovered from the organs of dead bodies found in water.